1993
DOI: 10.1007/bf02542597
|View full text |Cite
|
Sign up to set email alerts
|

Squalene recovery from olive oil deodorizer distillates

Abstract: Olive oil deodorization distillate contains squalene in a concentration range of 10 to 30 wt%. A process for its recovery by supercritical carbon dioxide extraction is described. The process consists mainly of converting the free fatty acids and the methyl and ethyl esters normally occurring in this by‐product into their corresponding triglycerides. The latter are then extracted with supercritical carbon dioxide to provide a highly enriched squalene fraction. The process has been carried out on a pilot‐plant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
83
0
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(93 citation statements)
references
References 8 publications
3
83
0
3
Order By: Relevance
“…He concluded that the separation factor for squalene/ -tocopherol varied between a value of 4 at low squalene concentrations (0.5 wt %), to a value of 1 at high squalene concentrations (85 wt %), at pressures ranging from 200 to 300 bar and temperatures ranging from 70 to 100 ºC. Bondioli and coworkers (Bondioli et al, 1993) esterified FFAs into their corresponding glycerides and then applied a supercritical carbon dioxide extraction to produce a squaleneenriched fraction (purity 90.0%, yield 91.1%), but from olive oil deodorizer distillates.…”
Section: Supercritical Fluid Extraction (Sfe)mentioning
confidence: 99%
“…He concluded that the separation factor for squalene/ -tocopherol varied between a value of 4 at low squalene concentrations (0.5 wt %), to a value of 1 at high squalene concentrations (85 wt %), at pressures ranging from 200 to 300 bar and temperatures ranging from 70 to 100 ºC. Bondioli and coworkers (Bondioli et al, 1993) esterified FFAs into their corresponding glycerides and then applied a supercritical carbon dioxide extraction to produce a squaleneenriched fraction (purity 90.0%, yield 91.1%), but from olive oil deodorizer distillates.…”
Section: Supercritical Fluid Extraction (Sfe)mentioning
confidence: 99%
“…Methods using a preliminary fractionation of samples, procedure that simplifies the analysis have been developed. Analysis of squalene in edible oils is predominantly achieved by chromatographic techniques (Gas Chromatography (GC) or Reversed-Phase High-Performance Liquid Chromatography (RP-HPLC)), after saponification of triglycerides, solvent extraction of the unsaponifiable fraction, and eventually isolation of the hydrocarbon fraction by Column Chromatography (CC) or Thin Layer Chromatography (TLC) [16][17][18][19][20][21]. The direct injection of olive oil in the injector port has been applied [22], as well as HPLC coupled with GC [23] or HPLC coupled to electrospray tandem mass spectrometry [24].…”
Section: Introductionmentioning
confidence: 99%
“…Generally SQ in foods, oils and fats is determined by titrimetric (Association of Official Analytical Chemists (AOAC). Official method of analysis (OMA), 1999) or chromatographic procedures (Bondioli, Mariani, Lanzani, Fedeli, & Muller, 1993;Cert, Moreda, & Pérez-Camino, 2000;De Leonardis, Macciola, & De Felice, 1998) and some studies recommended SPE for sample preparation (Grigoriadou, Androulaki, Psmiadou, & Tsimidou, 2007;Popa, Bȃbeanu, Popa, Nitȃ, & Dinu-Pârvu, 2015). The modern analytic methods used for SQ determination in various types of food are the gas-chromatography (GC) (Bueno, Casas, García, & González, 2005), alone or coupled with high performance liquid chromatography (HPLC) (Esche, Müller, & Engel, 2013;Grob, Artho, & Mariani, 1992;Villén, Blanch, Castillo, & Herraiz, 1998), or HPLC alone (Nenadis & Tsimidou, 2002;Sagratini et al, 2012) or coupled to mass spectrometry (HPLC/MS) (Di Stefano et al, 2012;Mountfort, Bronstein, Archer, & Jickells, 2007;Russo, Muzzalupo, Perri, & Sindona, 2010).…”
Section: Introductionmentioning
confidence: 99%